2022
DOI: 10.3390/su14073753
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Self-Perceived Employability on Sustainable Career Development in Times of COVID-19: Two Mediating Paths

Abstract: The outbreak of COVID-19 added further stress to individuals’ work life, and employability may be especially important to help individuals to pursue sustainable career success in such a context. However, previous studies that examined the impact and the mechanisms of employability on sustainable career success are lacking, especially in the context of pandemic threat. Based on conservation of resource theory (COR), the current study aims to explore whether and how employability, as an important resource, reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Furthermore, Deng et al observed that organizational identification not only dampened the positive effect of perceived external employability on turnover intention, but also amplified the negative impact of perceived organizational growth on turnover intention. Moreover, Zhou et al (2022) noted that employees' career commitment mediated its effect on their work engagement in times of COVID-19. These findings agreed with this research result when, in times of crisis, curriculum innovation and its positive implication on employability is a necessity, leading students to change in their specialization and career paths.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Deng et al observed that organizational identification not only dampened the positive effect of perceived external employability on turnover intention, but also amplified the negative impact of perceived organizational growth on turnover intention. Moreover, Zhou et al (2022) noted that employees' career commitment mediated its effect on their work engagement in times of COVID-19. These findings agreed with this research result when, in times of crisis, curriculum innovation and its positive implication on employability is a necessity, leading students to change in their specialization and career paths.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, individual sustainable careers include three elements: happiness, health and productivity [5] and a recent review stated that future research should pay more attention to happiness (e.g., vigor) and productivity (e.g., level of pay) [13]. Vigor is typically conceptualized as being full of energy and having the willingness to make efforts in work, and is an important subjective career experience indicating employees' sustainable careers [32,33]. Meanwhile, sustainable careers are embodied by objective career experiences such as level of pay [10,34], which refers to various forms of remuneration obtained by employees for providing services to their organizations [35].…”
Section: Hypothesis Development 221 Positive Affectivity and Sustaina...mentioning
confidence: 99%
“…In particular, first- and second-year students showed a lack of engagement with this concept (Tymon, 2013). Moreover, Zhou et al. (2022) highlighted the significant effect of self-perceived employability (SPE) during stressful situations like the pandemic, because it can help employers and employees understand how to stay employable, despite the negative impacts of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, first-and second-year students showed a lack of engagement with this concept (Tymon, 2013). Moreover, Zhou et al (2022) highlighted the significant effect of self-perceived employability (SPE) during stressful situations like the pandemic, because it can help employers and employees understand how to stay employable, despite the negative impacts of the pandemic. In addition, different factors impact SPE such as self-confidence, self-esteem, self-efficacy, ambition and university commitment (Baruch et al, 2020;Jackson and Tomlinson, 2020;Donald et al, 2019;Alvarez-Gonz alez et al, 2017;Chou et al, 2012;Alibaygi et al, 2013;Maiolo et al, 2013;Kim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%